Neither Idolatry nor Iconoclasm: A Critical Essentialism for Catholic Feminist Theology - Dallavalle, Nancy A. (Horizons, 1998)
Following the work of gender theorists who find the terms "male" and "female" to be socially constructed, feminist theology has tended to repudiate essentialism. The position that results is one of agnosticism about biological sexuality, a position that is only reinforced by the essentialist excesses that ground the discussion of the "psycho-physical structure" of women found in official Catholic teaching. This article suggests that the polarity of feminist theology and official Catholic teaching on questions of sex and gender can be overcome by using the framework of a "critical essentialism," a position that retrieves the Catholic theological tradition of reflection on "male" and "female" while allowing its claims to be appropriately winnowed by the insights of gender theorists.